2023
DOI: 10.3389/fphys.2023.957758
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic optic disc height combined with the optic nerve sheath diameter as a promising non-invasive marker of elevated intracranial pressure

Abstract: Background/aim: Patients with elevated intracranial pressure (ICP) tend to have optic disc edema and a thicker optic nerve sheath diameter (ONSD). However, the cut-off value of the optic disc height (ODH) for evaluating elevated ICP is not clear. This study was conducted to evaluate ultrasonic ODH and to investigate the reliability of ODH and ONSD for elevated ICP.Methods: Patients suspected of having increased ICP and who underwent a lumbar puncture were recruited. ODH and ONSD were measured before lumbar pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Elevation of the optic disc can be measured by point-of-care US (US-ODE) as well. A recent study revealed, that the combination of US-ONSD and US-ODE might be a promising diagnostic tool to monitor elevated ICP in adults ( Yu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of the optic disc can be measured by point-of-care US (US-ODE) as well. A recent study revealed, that the combination of US-ONSD and US-ODE might be a promising diagnostic tool to monitor elevated ICP in adults ( Yu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%